Reticulocytosis: the unevaluated parameter in neonatal jaundice requiring phototherapy - Xavier, Rose; V. C., Manoj; T. M., Sanjeev Kumar; Cherian, Vinod J. (International Journal of Contemporary Pediatrics, 2016)
Background:Majority of the jaundiced neonates requiring phototherapy do not have an identifiable cause for the jaundice. Reticulocyte count more than 4% on day 3 of life is called reticulocytosis in neonates. So far no studies have evaluated the prevalence of reticulocytosis among jaundiced neonates requiring phototherapy. Objective of the study was to identify babies with only reticulocytosis as cause for jaundice and identify factors contributing to reticulocytosis. Methods: An observational study was carried out over a period of one year in the neonatal unit of a tertiary care hospital on 200 jaundiced neonates requiring phototherapy for determining the incidence of jaundice with unknown etiology. This data was analysed for prevalence of reticulocytosis and its contributing factors. Results:67 of 200 babies with jaundice had reticulocytosis. An etiology for the reticulocytosis was found in 37 babies. 12 of the remaining 30 babies had dehydration (weight loss more than 10%) contributing to jaundice. 18 babies had no identifiable cause for the reticulocytosis. Mildly significant correlation was found with sibling history of neonatal jaundice (p = 0.052). No significant correlation was found with any other contributing factors. Conclusions:Reticulocyte count should be done for any baby with jaundice requiring phototherapy. Screening for irregular antibodies and genetic studies need to be promoted along with routine tests, to identify the cause for reticulocytosis after working out the costs involved.